Ellipsoidal polyhedral MOF (Metal Organic Framework) derived phosphide as well as preparation method and application thereof

By introducing Re atoms into MOFs-derived phosphides, an ellipsoidal polyhedral Re-Co2P catalyst was prepared, which solved the problem of insufficient electrolytic hydrolysis oxygen evolution reaction performance in alkaline electrolytes, and significantly improved catalytic activity and conductivity , achieving efficient electrocatalytic decomposition of water and hydrogen production.

CN119145004APending Publication Date: 2024-12-17JINHUA VOCATIONAL TECH COLLEGE
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411639345.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The performance of existing MOFs-derived phosphides in alkaline electrolyte hydrolyzed oxygen evolution reaction (OER) is insufficient, especially in terms of catalytic activity.

Method used

By mixing soluble cobalt salt, 2-methylimidazole and alcohol solvent for coordination reaction, a Co-MOF-containing material was obtained, and then solvothermal reaction was performed with soluble rhenium salt, Re atoms were introduced, and then in situ phosphating was performed to prepare Ellipsoidal polyhedral MOF-derived phosphide Re-Co2P catalyst.

Benefits of technology

Improve the conductivity and catalytic kinetic properties of the catalyst, enhance the catalytic activity of electrolytic water, especially the hydrogen/oxygen evolution reaction (HER/OER) and total hydrolysis (OWS) electrocatalytic activity in alkaline electrolytes, achieving excellent Catalytic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145004A_ABST
    Figure CN119145004A_ABST
Patent Text Reader

Abstract

The invention provides an ellipsoidal polyhedral MOF (Metal Organic Framework) derived phosphide as well as a preparation method and application thereof, and relates to the technical field of electro-catalytic materials. The preparation method comprises the following steps: mixing soluble cobalt salt, 2-methylimidazole and an alcohol solvent for a coordination reaction, and mixing an obtained solution containing a Co-MOF material with soluble rhenium salt for a solvothermal reaction to obtain a Re-Co-MOF material; the Re-Co-MOF material is subjected to in-situ phosphorization, and the ellipsoidal polyhedron-shaped MOF derivative phosphide is obtained. Re atoms are introduced into the Co-MOF-derived phosphide Co2P, the catalytic microenvironment of the Co2P can be adjusted, the electronic structure of the Co2P can be adjusted and controlled, the conductivity of the Co2P is improved, meanwhile, the surface potential energy in the synthesis process of the Co2P is adjusted and controlled, the morphology of the Co2P is optimized, and then the catalytic activity of the Co2P is improved. The MOF derivative phosphide prepared by the invention has excellent water electrolysis hydrogen / oxygen evolution activity and full hydrolysis electrocatalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic materials, and in particular to an ellipsoidal polyhedron MOF-derived phosphide and a preparation method and application thereof. Background Art

[0002] Due to the characteristics of hydrogen being clean and having high energy density, it is regarded as a potential energy source to replace traditional fossil fuels, and the development of hydrogen production methods has also attracted the attention of a large number of researchers. Among the many hydrogen production strategies, electrocatalytic water decomposition to produce hydrogen is considered to be an efficient method because it can produce high-purity hydrogen at low cost. However, the slow kinetics of electrode materials greatly hinder the efficiency of electrocatalytic water decomposition to produce hydrogen. At present, precious metals such as Pt are considered to be excellent electrode materials for electrocatalytic water decomposition to produce hydrogen. However, their high cost and scarcity hinder their commercial application. Therefore, it is very important to design and prepare low-cost, high-performance electrode materials for electrocatalytic water decomposition to produce hydrogen.

[0003] MOFs-derived materials, such as MOFs-derived oxides, MOFs-derived sulfides, MOFs-derived phosphides, etc., are considered as high-performance candidate materials for electrocatalytic water decomposition to produce hydrogen due to their large specific surface area, adjustable pore size and excellent catalytic activity. Among the many MOFs-derived materials, MOFs-derived phosphides are considered to be superior materials for electrocatalytic water decomposition to produce hydrogen due to their excellent conductivity. At present, although various types of phosphide electrocatalysts have been synthesized using MOFs as precursors, the catalytic activity of MOFs-derived phosphides is still unsatisfactory, especially the performance of oxygen evolution reaction (OER) in water electrolysis in alkaline electrolytes needs to be further improved. Summary of the invention

[0004] In view of this, the object of the present invention is to provide an ellipsoidal polyhedron MOF-derived phosphide and a preparation method and application thereof. The ellipsoidal polyhedron MOF-derived phosphide prepared by the present invention has excellent electrolytic water catalytic performance.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing an ellipsoidal polyhedron MOF-derived phosphide, comprising the following steps: A soluble cobalt salt, 2-methylimidazole and an alcohol solvent are mixed to carry out a coordination reaction to obtain a solution containing a Co-MOF material; The solution containing the Co-MOF material is mixed with a soluble rhenium salt to perform a solvothermal reaction to obtain a Re-Co-MOF material; The Re-Co-MOF material is in-situ phosphated to obtain the ellipsoidal polyhedron-shaped MOF-derived phosphide.

[0006] Preferably, the molar ratio of cobalt element to 2-methylimidazole in the soluble cobalt salt is 1:8; the temperature of the coordination reaction is room temperature, and the time is 20 to 40 minutes.

[0007] Preferably, the soluble rhenium salt comprises NH4ReO4.

[0008] Preferably, the molar ratio of the cobalt element in the soluble cobalt salt to the rhenium element in the soluble rhenium salt used to prepare the solution containing the Co-MOF material is 1:(0.1~0.25).

[0009] Preferably, the temperature of the solvent thermal reaction is 130-150° C., and the insulation time is 10-16 hours.

[0010] Preferably, the phosphating agent used in the in-situ phosphating is NaH2PO2.

[0011] Preferably, the temperature of the in-situ phosphating is 300-400° C., and the holding time is 1-3 hours.

[0012] The present invention provides an ellipsoidal polyhedron-shaped MOF-derived phosphide prepared by the preparation method described in the above technical solution.

[0013] The present invention provides the use of the ellipsoidal polyhedron MOF-derived phosphide described in the above technical solution in the electrocatalytic decomposition of water to produce hydrogen.

[0014] Preferably, the electrolyte for electrocatalytic decomposition of water to produce hydrogen is a KOH aqueous solution, and the concentration of the KOH aqueous solution is 1-3 mol / L.

[0015] The present invention provides a method for preparing an ellipsoidal polyhedron MOF-derived phosphide. The present invention prepares the ellipsoidal polyhedron MOF-derived phosphide by combining a solvent thermal process and a phosphating process. During the solvent thermal reaction, Re atoms are introduced into the Co-MOF material, and the surface of the obtained Re-Co-MOF material becomes rough; then, after an in-situ phosphating process, a Re-Co2P composite material is obtained, and presents an ellipsoidal polyhedron structure, that is, the ellipsoidal polyhedron MOF-derived phosphide. Compared with the prior art, the present invention has the following beneficial effects: The present invention introduces Re atoms into the Co-MOF-derived phosphide Co2P, which can not only adjust the catalytic microenvironment of Co2P, but also regulate the electronic structure of Co2P and improve its conductivity, thereby improving the catalytic kinetics of Co2P; and the injection of Re atoms can also regulate the surface potential energy during the synthesis of Co2P, thereby optimizing its morphology. The ellipsoidal polyhedron shape can provide more reactive sites, which is more conducive to the improvement of catalytic activity.

[0016] The results of the embodiment show that the ellipsoidal polyhedral MOF-derived phosphide (Re-Co2P catalyst) prepared by the present invention has a high conductivity in alkaline electrolyte and 10 mA·cm -2 The electrocatalytic activities of hydrogen / oxygen evolution reaction (HER / OER) under the above conditions were 57 mV and 235 mV, respectively, at 10 mA cm -2 The electrocatalytic activity of overall water splitting (OWS) under the given conditions reached 1.50V. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the process for preparing ellipsoidal polyhedron-shaped MOF-derived phosphide (Re-Co2P) and scanning electron microscope (SEM) images of the material. Figure 1 (a) is a schematic diagram of the process for preparing Re-Co2P, (b) and (c) are scanning electron micrographs of Co-MOF prepared in Example 1, (d) and (e) are scanning electron micrographs of Re prepared in Example 3 0.2 -SEM images of Co-MOF composite materials, (f) and (g) are Re prepared in Example 3 0.2 -SEM image of Co2P composite material; Figure 2 X-ray diffraction (XRD) patterns and full X-ray photoelectron spectroscopy (XPS) of the Re-Co2P composite materials and Co2P materials prepared in the examples and comparative examples, Figure 2 (a) is the XRD pattern, (b) is the XPS result of Co 2p in Co2P and Re-Co2P, (c) is the XPS spectrum of P 2p in Co2P and Re-Co2P, and (d) is the XPS result of Re 4f in Re-Co2P composite material; Figure 3 HER performance of Re-Co2P composite materials and Co2P materials prepared in Examples and Comparative Examples, Figure 3 (a) is the LSV curve, (b) is 10mA·cm -2 and 50mA·cm -2 , (c) is the Tafel slope, (d) is the Cdl graph, (e) is the EIS graph, and (f) is the Re 0.2 -HER stability of Co2P composites; Figure 4 The OER and OWS performances of the Re-Co2P composite materials and Co2P materials prepared in the examples and comparative examples are shown in FIG. Figure 4 (a) shows the LSV curves of Re-Co2P composite material and Co2P material, (b) shows the LSV curves of Re-Co2P composite material and Co2P material at 10 mA·cm -2 and 50mA·cm -2The overpotential under (c) is the Tafel slope of Re-Co2P composite material and Co2P material, (d) is the EIS graph of Re-Co2P composite material and Co2P material, and (e) is the Re 0.2 -Co2P stability, (f) is Re 0.2 - OWS performance of Co2P and noble metal catalysts; Figure 5 Cyclic voltammetry curves at different scan rates. Figure 5 (a) to (e) correspond to Co2P, Re 0.1 -Co2P、Re 0.15 -Co2P、Re 0.2 -Co2P、Re 0.25 -Co2P. DETAILED DESCRIPTION

[0018] The present invention provides a method for preparing an ellipsoidal polyhedron MOF-derived phosphide, comprising the following steps: A soluble cobalt salt, 2-methylimidazole and an alcohol solvent are mixed to carry out a coordination reaction to obtain a solution containing a Co-MOF material; The solution containing the Co-MOF material is mixed with a soluble rhenium salt to perform a solvothermal reaction to obtain a Re-Co-MOF material; The Re-Co-MOF material is in-situ phosphated to obtain the ellipsoidal polyhedron-shaped MOF-derived phosphide.

[0019] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.

[0020] The present invention mixes a soluble cobalt salt, 2-methylimidazole and an alcohol solvent for coordination reaction to obtain a solution containing Co-MOF material. In the present invention, the soluble cobalt salt is preferably Co(NO3)2·6H2O, and the molar ratio of cobalt element to 2-methylimidazole in the soluble cobalt salt is preferably 1:8. In the present invention, the alcohol solvent is preferably methanol, and the total concentration of soluble cobalt salt and 2-methylimidazole in the mixed solution obtained by mixing is preferably 0.225mmol / mL. In the present invention, the mixing method is preferably: adding a soluble cobalt salt to part of the alcohol solvent, stirring for 15 minutes, to obtain solution A; adding 2-methylimidazole to the remaining alcohol solvent, stirring for 15 minutes, to obtain solution B; mixing the solution A with the solution B.

[0021] In the present invention, the temperature of the coordination reaction is preferably room temperature, the time is preferably 20 to 40 minutes, and the coordination reaction is preferably carried out under stirring. After the coordination reaction, a solution containing Co-MOF material (metal organic framework material) is obtained.

[0022] After obtaining the solution containing Co-MOF material, the present invention mixes the solution containing Co-MOF material with a soluble rhenium salt for a solvothermal reaction to obtain Re-Co-MOF material. In the present invention, the soluble rhenium salt preferably includes NH4ReO4 (ammonium perrhenate). In the present invention, the molar ratio of the cobalt element in the soluble cobalt salt used to prepare the solution containing Co-MOF material to the rhenium element in the soluble rhenium salt is preferably 1: (0.1~0.25), which can be 1: 0.1, 1: 0.15, 1: 0.2 or 1: 0.25. In the present invention, the method of mixing the solution containing Co-MOF material with the soluble rhenium salt is preferably: adding a soluble rhenium salt to the solution containing Co-MOF material and stirring for 30 minutes.

[0023] In the present invention, the temperature of the solvothermal reaction is preferably 130-150°C, which can be 130°C, 140°C or 150°C, and the holding time is preferably 10-16h, more preferably 10-12h. In the present invention, the solvothermal reaction is also preferably added with carbon cloth, that is, the solution containing the Co-MOF material is mixed with a soluble rhenium salt to obtain a mixed solution and a piece of carbon cloth are placed in a reactor for solvothermal reaction, and the carbon cloth serves as a growth substrate for the Re-Co-MOF material. During the solvothermal reaction, Re atoms are injected into the Co-MOF material, and the surface of the resulting Re-Co-MOF material becomes rougher than that of the Co-MOF material.

[0024] After the solvothermal reaction is completed, the present invention preferably washes the obtained product with deionized water and anhydrous ethanol three times respectively.

[0025] After obtaining the Re-Co-MOF material, the present invention performs in-situ phosphating on the Re-Co-MOF material to obtain the ellipsoidal polyhedron-shaped MOF-derived phosphide. In the present invention, the phosphating agent used in the in-situ phosphating is preferably NaH2PO2, and the molar ratio of the cobalt element in the Re-Co-MOF material to the phosphorus element in the phosphating agent is preferably 1: (4~5); the temperature of the in-situ phosphating is preferably 300~400℃, which can be 300℃, 350℃ or 400℃, and the insulation time is preferably 1~3h, which can be 1h, 2h or 3h. In the present invention, the in-situ phosphating is preferably carried out in a tubular furnace, and the specific operation of the in-situ phosphating is preferably: placing the NaH2PO2 and Re-Co-MOF material in the upstream (inlet side) and downstream (outlet side) of the tubular furnace respectively, introducing argon as a protective gas, heating to 300~400℃ at a rate of 3℃ / min, and keeping warm for phosphating. During the insulation process, NaH2PO2 decomposes to generate PH3, and PH3 reacts with the Re-Co-MOF material as follows: Re-Co-MOF+PH3→Re-Co2P+H2.

[0026] At present, there are still many challenges in the controlled synthesis of MOF-derived complexes with regular morphology and high catalytic activity using simple chemical methods, especially the synthesis of MOF-derived phosphides has problems such as cumbersome synthesis steps, irregular morphology, and uneven size. The present invention adopts a catalytic microenvironment regulation strategy, combines solvent thermal and in-situ phosphating methods to inject Re atoms into Co-MOF-derived Co2P, and successfully constructs an ellipsoidal polyhedron-shaped high-performance electrocatalyst Re-Co2P material. The Re-Co2P material obtained by the method of the present invention has a regular morphology and uniform size, and the ellipsoidal polyhedron has a large contact area, which can increase the contact area between the catalyst and the electrolyte, thereby further improving its catalytic performance.

[0027] The present invention provides an ellipsoidal polyhedron-shaped MOF-derived phosphide prepared by the preparation method described in the above technical solution. In the present invention, the spherical polyhedron-shaped MOF-derived phosphide is Co2P injected with Re atoms, and the Co2P is a Co-MOF-derived phosphide.

[0028] The present invention provides the use of the ellipsoidal polyhedron MOF-derived phosphide described in the above technical solution in the electrocatalytic decomposition of water to produce hydrogen.

[0029] In the present invention, the electrolyte for electrocatalytic decomposition of water to produce hydrogen is preferably a KOH aqueous solution, and the concentration of the KOH aqueous solution is preferably 1-3 mol / L.

[0030] The present invention injects Re atoms into Co-MOF-derived Co2P through a catalytic microenvironment regulation strategy, and the resulting ellipsoidal polyhedron MOF-derived phosphide (Re-Co2P) has efficient electrolytic water catalytic performance. Thanks to the fact that injecting Re atoms into Co2P can regulate the catalytic microenvironment, enhance conductivity and improve the electron transfer ability of Co2P, the Re-Co2P catalyst has excellent hydrogen and oxygen evolution activity. Experimental and density functional theory data confirm that the introduction of Re atoms into Co2P can regulate the electronic structure and promote the charge localization redistribution of Co2P, thereby optimizing the adsorption energy during water electrolysis.

[0031] In order to further illustrate the present invention, the ellipsoidal polyhedron MOF-derived phosphide provided by the present invention and its preparation method and application are described in detail below in combination with examples, but they should not be understood as limiting the scope of protection of the present invention.

[0032] Example 1 An ellipsoidal polyhedral MOF-derived phosphide (Re 0.1 -Co2P composite material), the preparation method is as follows: 0.5 mmol Co(NO3)2·6H2O was added to 10 mL of methanol and stirred for 15 min to obtain solution A; 4 mmol 2-methylimidazole was added to 10 mL of methanol and stirred for 15 min to obtain solution B; then solution A and solution B were mixed and stirred for 20 min to obtain a solution containing Co-MOF material, named solution C.

[0033] Then, 0.05 mmol NH4ReO4 was added to solution C and stirred for 30 min. The resulting solution and a piece of carbon cloth (2 cm × 2 cm) were placed in a reactor and kept at 130 °C for 12 h. The sample was then washed three times with deionized water and anhydrous ethanol to obtain a Re-Co-MOF material (grown on carbon cloth), recorded as Re 0.1 -Co-MOF.

[0034] The growth obtained above has Re 0.1 -Co-MOF carbon cloth and 200 mg NaH2PO2 were placed in the downstream and upstream of the tube furnace, respectively, and then the tube furnace was heated to 350 ° C (heating rate 3 ° C / min) under argon flow for 2 h to obtain the ellipsoidal polyhedral MOF-derived phosphide, recorded as Re 0.1 -Co2P composite materials.

[0035] Example 2 The amount of NH4ReO4 added was adjusted to 0.075 mmol, and the rest was the same as in Example 1 to obtain an ellipsoidal polyhedral MOF-derived phosphide, denoted as Re 0.15 -Co2P composite materials.

[0036] Example 3 The amount of NH4ReO4 added was adjusted to 0.1 mmol, and the rest was the same as in Example 1 to obtain an ellipsoidal polyhedral MOF-derived phosphide. The Re-Co-MOF material obtained in Example 3 is denoted as Re 0.2 -Co-MOF, the obtained ellipsoidal polyhedron-shaped MOF-derived phosphide is denoted as Re 0.2 -Co2P composite materials.

[0037] Example 4 The amount of NH4ReO4 added was adjusted to 0.125 mmol, and the rest was the same as in Example 1 to obtain an ellipsoidal polyhedral MOF-derived phosphide, denoted as Re 0.25 -Co2P composite materials.

[0038] Comparative Example 1 The amount of NH4ReO4 added was adjusted to 0 mmol, and the rest was the same as in Example 1 to obtain a MOF-derived phosphide, which was recorded as Co2P.

[0039] Figure 1 (a) shows the schematic diagram of the preparation of Re-Co2P composites by combining hydrothermal process and phosphating process. Figure 1 (b) and (c) are scanning electron microscope (SEM) images of the Co-MOF prepared in Example 1. The scanning electron microscope is used to measure the morphology of the prepared samples, such as Figure 1 As shown in (b) and (c), the prepared Co-MOF has a polyhedral structure, and the surface of Co-MOF is composed of layers of thin sheets. After the Re atoms are introduced into Co-MOF, Re 0.2 -The surface of the Co-MOF composite material becomes rough (e.g. Figure 1 As shown in (d) and (e). After the in-situ phosphating process, Re 0.2 -Co2P composites present a polyhedral structure (e.g. Figure 1 In particular, after the phosphating process, Re 0.2 -Surface specific Re of Co2P composites 0.2 -Co-MOF materials are rough, which may provide multiple reaction sites during water electrolysis.

[0040] Figure 2 (a) shows the X-ray diffraction (XRD) data of the Re-Co2P composite materials and Co2P materials prepared in the examples and comparative examples. As shown in the figure, the (020), (200) and (211) diffraction peaks belong to Co2P (JCPDS No.: 32-0306); after the introduction of Re atoms into Co2P, the intensity of the (020) peak decreases, which indicates that the injection of Re atoms into Co2P affects the crystal structure of Co2P. XPS results of Co 2p in pure Co2P prepared in comparative example 1 ( Figure 2 (b) shows the Co 2p 2 / 3 (782.27 eV) and Co 2p 1 / 2 (798.43eV) and two satellite peaks at 786.40eV and 803.57eV respectively. XPS spectrum of P 2p in pure Co2P ( Figure 2 (c) shows a peak at 134.03 eV. Figure 2 (d) shows the XPS results of Re 4f in the Re-Co2P composite material. The peaks at 42.56eV, 45.13eV, and 47.55eV belong to Re 4f 7 / 2 、Re 4f 5 / 2 and ReO4 - . Figure 2 Re-Co2P in (b) to (d) is Re 0.2-Co2P. Compared with pure Co2P, the XPS spectra of Co 2p and P 2p in Re-Co2P composites show obvious shifts, indicating that the implantation of Re atoms into Co2P can greatly change the electronic structure of Co2P. Therefore, all these results prove the successful preparation of Re-Co2P composites.

[0041] Figure 3 The hydrogen evolution activity (HER) of the Re-Co2P composite material and the Co2P material prepared in the examples and comparative examples, the electrolyte was 1 mol / L KOH aqueous solution. Figure 3 (a) shows the linear sweep voltammetry (LSV) curve of the sample after iR correction at 10 mA cm -2 Under these conditions, Co2P, Re 0.1 -Co2P、Re 0.15 -Co2P、Re 0.2 -Co2P、Re 0.25 -The overpotentials of Co2P and Pt are 279mV, 135mV, 87mV, 57mV, 65mV and 45mV respectively (e.g. Figure 3 In particular, Re 0.2 -Co2P composite material at 50mA·cm -2 The catalytic activity under the condition of 100 % kinetic energy was 115 mV, which is much higher than that of Co2P (450 mV @ 50 mA cm -2 )、Re 0.1 -Co2P(262mV@50mA·cm -2 )、Re 0.15 -Co2P(186mV@50mA·cm -2 )、Re 0.25 -Co2P(154mV@50mA·cm -2 ), which is also close to Pt (107mV@50mA·cm -2 ). 0.2 -The HER performance of the Co2P composite material is better than that of other samples, which may be because the injection of an appropriate amount of Re atoms into Co2P can adjust the electronic structure and improve the catalytic activity of Co2P. The Tafel slope results are shown in Figure 3 As shown in (c), Re 0.2 -Tafel slope of Co2P composite (65mV·dec -1 ) is less than Co2P (193mV·dec -1 )、Re 0.1 -Co2P(127mV·dec -1 )、Re 0.15 -Co2P(98mV·dec -1) and Re 0.25 -Co2P(85mV·dec -1 ). This result shows that Re 0.2 -Co2P composites exhibited superior catalytic kinetics in the electrocatalytic hydrogen evolution process. In addition, the cyclic voltammetry curves at different scan rates were also tested ( Figure 5 As shown, Figure 5 (a) to (e) correspond to Co2P, Re 0.1 -Co2P、Re 0.15 -Co2P、Re 0.2 -Co2P、Re 0.25 -Co2P) to evaluate the electrochemical double layer capacitance (Cdl) of the prepared samples.

[0042] like Figure 3 As shown in (d), Re 0.2 -The Cdl of the Co2P composite is 7.67mF·cm -2 , higher than Co2P (0.31mF·cm -2 )、Re 0.1 -Co2P(1.90mF·cm -2 )、Re 0.15 -Co2P(3.43mF·cm -2 ) and Re 0.25 -Co2P(4.68mF·cm -2 ), indicating that it will produce abundant active sites in the hydrogen production process. In order to evaluate the charge transfer performance of the prepared samples, electrochemical impedance spectroscopy (EIS) was performed, as shown in Figure 3 As shown in (e), by comparison, Re 0.2 -Charge transfer resistance (R ct ) is smaller than that of other samples, which indicates that it has excellent charge transfer performance in the HER process. This result also shows that the introduction of an appropriate amount of Re atoms into Co2P can not only improve the conductivity but also promote the charge transfer performance of Co2P. 0.2 The stability of hydrogen evolution in water electrolysis of -Co2P composite materials was tested. Figure 3 As shown in (f), after more than 90 hours of testing, Re 0.2 -Co2P exhibits remarkable HER activity, indicating its excellent catalytic durability.

[0043] Figure 4 The oxygen evolution performance (OER) of the Re-Co2P composite material and the Co2P material prepared in the examples and comparative examples is shown, and the electrolyte is a 1 mol / L KOH aqueous solution. Figure 4 As shown, Re0.2 -Co2P composites have better oxygen evolution activity than other samples. Figure 4 (a) shows the linear sweep voltammetry (LSV) curve of the sample at 10 mA cm -2 Under the condition, Re 0.2 -The overpotential of the Co2P composite is 235mV ( Figure 4 (b)), much lower than Co2P (385mV) and Re 0.1 -Co2P (295mV), Re 0.15 -Co2P (287mV), Re 0.25 -Co2P (259mV) and RuO2 (326mV). Especially at 50mA·cm -2 Under the condition of 0.2 -Co2P composite still shows an excellent oxygen evolution activity of 345 mV, which is better than RuO2 (460 mV) and Co2P (479 mV). Figure 4 (c) shows the Tafel slope of the prepared sample. In comparison, Re 0.2 -The Tafel slope of the Co2P catalyst is 125 mV·dec -1 , lower than RuO2 (205mV·dec -1 )、Co2P(211mV·dec -1 )、Re 0.1 -Co2P(199mV·dec -1 )、Re 0.15 -Co2P(165mV·dec -1 ) and Re 0.25 -Co2P(137mV·dec -1 ). 0.2 -Co2P has a lower Tafel slope, which indicates that it has excellent catalytic kinetics in the OER process. Figure 4 As shown in (d), compared with other catalysts, Re 0.2 -R of Co2P ct This indicates that it has an excellent electron transfer rate between the electrode and the electrolyte. 0.2 -The cycling stability of Co2P was evaluated as Figure 4 As shown in (e), Re 0.2 -Co2P composites showed good oxygen evolution performance after more than 90 hours of testing.

[0044] In order to evaluate the overall hydrolysis performance of the prepared samples, two kinds of Re 0.2-Co2P composite materials were used as cathode and anode electrodes of OWS, and the electrolyte was 1 mol / L KOH aqueous solution. Figure 4 As shown in (f), Re 0.2 -Co2PǀǀRe 0.2 The total hydrolysis voltage of the Co2P electrode is 1.50 V @ 10 mA cm -2 and 1.65V@50mA·cm -2 , lower than that of PtǀǀRuO2 catalyst (1.56V@10mA·cm -2 and 1.75V@50mA·cm -2 ).

[0045] From the above examples, it can be seen that the present invention constructs a high-performance water separation electrocatalyst by injecting Re atoms into Co2P derived from Co-MOF to regulate the catalytic microenvironment. Taking advantage of the fact that injecting Re atoms into Co2P can regulate the catalytic microenvironment, improve the conductivity and enhance the charge transfer ability of Co2P, the optimized Re-Co2P catalyst has a high conductivity at 10 mA cm -2 The HER / OER values ​​under the condition of 10 mA cm-1 can reach 57 mV and 235 mV respectively. -2 The full hydrolysis voltage under the condition can reach 1.50V, showing excellent catalytic performance. The present invention is an effective method for constructing a high-efficiency water separation catalyst by injecting metal atoms into MOFs-derived materials to adjust the catalytic microenvironment.

[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an ellipsoidal polyhedron MOF-derived phosphide, comprising the following steps: A soluble cobalt salt, 2-methylimidazole and an alcohol solvent are mixed to carry out a coordination reaction to obtain a solution containing a Co-MOF material; The solution containing the Co-MOF material is mixed with a soluble rhenium salt to perform a solvothermal reaction to obtain a Re-Co-MOF material; The Re-Co-MOF material is in-situ phosphated to obtain the ellipsoidal polyhedron-shaped MOF-derived phosphide.

2. The preparation method according to claim 1, characterized in that: The molar ratio of cobalt element to 2-methylimidazole in the soluble cobalt salt is 1:8; the temperature of the coordination reaction is room temperature, and the time is 20 to 40 minutes.

3. The preparation method according to claim 1, characterized in that: The soluble rhenium salt includes NH4ReO4.

4. The preparation method according to claim 1 or 3, characterized in that: The molar ratio of the cobalt element in the soluble cobalt salt to the rhenium element in the soluble rhenium salt used to prepare the solution containing the Co-MOF material is 1:(0.1~0.25).

5. The preparation method according to claim 1 or 3, characterized in that: The temperature of the solvent thermal reaction is 130-150° C., and the insulation time is 10-16 hours.

6. The preparation method according to claim 1, characterized in that: The phosphating agent used in the in-situ phosphating is NaH2PO2.

7. The preparation method according to claim 1 or 6, characterized in that: The temperature of the in-situ phosphating is 300-400° C., and the holding time is 1-3 hours.

8. The ellipsoidal polyhedron-shaped MOF-derived phosphide prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the ellipsoidal polyhedron-shaped MOF-derived phosphide according to claim 8 in electrocatalytic water decomposition to produce hydrogen.

10. The use according to claim 9, characterized in that: The electrolyte for electrocatalytic decomposition of water to produce hydrogen is a KOH aqueous solution, and the concentration of the KOH aqueous solution is 1-3 mol / L.

Citation Information

Patent Citations

  • Preparation method of polyhedral cobalt phosphide catalyst for hydrogen production through water electrolysis

    CN105107536A

  • Phosphorized metal-organic framework material, and preparation method and application thereof

    CN107602622A

  • Synthetic method of sheet-shape Co2P-carbon cloth composite material

    CN109295476A

  • Catalyst for producing furoic acid through electro-catalytic oxidation of furfural and preparation method and use method of catalyst

    CN114438524A

  • Preparation method and application of rare earth element doped 2D RE-Fe-MOF efficient integrated membrane electrode

    CN115747874A